Analysis of water, sanitation, and hygiene programs' impact on leprosy incidence in Indonesia: A secondary data analysis from the WHO Global Health Observatory - Soleman, Sani Rachman; Agusningtyas, Irena (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2025)
Declining rates of neglected tropical diseases, particularly leprosy, highlight the need for comprehensive policies addressing the incidence of this disease in Indonesia. This study aims to investigate the impact of water, sanitation, and hygiene (WASH) programs on the incidence of leprosy in the country's urban and rural areas.Data were collected from the WHO Global Health Observatory using a cross-sectional study design. The independent variables examined included open defecation-free programs, availability of handwashing facilities, and access to basic drinking water and sanitation services. The dependent variable was the incidence of leprosy in urban and rural settings. Data analysis was performed using independent T-tests and Pearson correlation coefficients with SPSS version 23.The findings revealed a significant decline in leprosy incidence in rural and moderately urban areas over a 14-year survey period, reflecting trends similar to those of WASH programs. Overall, WASH programs were found to be correlated with the incidence of leprosy in both urban and rural areas (p<0.001), while the significance of open defecation programs decreased (p=0.46). The Pearson correlation analysis indicated that the availability of handwashing facilities was positively correlated with leprosy incidence (r=0.58, p<0.001). In contrast, basic drinking water (r=-0.62, p<0.001) and basic sanitation services (r=-0.62, p<0.001) showed a negative association with leprosy incidence. In summary, WASH programs are crucial for controlling the spread of leprosy in Indonesia's urban and rural regions.  Keyword: Leprosy, WASH programs, urban and rural, Indonesia